The Harmony of Husband and Wife of Soldiers of Korem 132 / Tadulako from Perspective of the Islamic Law (State Institute for Islamic Studies Palu, 2019)
This study investigates the harmony of husband and wife of a soldier of Korem 132 / Tadulako from Perspective of Islamic Law. This research includes field research with the qualitative method. The data is collected by direct observation and interviews with such matters and thorough documentation of data in Korem 132 / Tadulako. Whereas the approach used in this study is the Religion approach, which is based on the questions of the Qur'an, and Al-Hadith, the approach of dis, which is based on the Discipline of Warrior Discipline in Law No. 26 of 1997. This analysis uses policing, but the analysis that departs from the facts and concrete events in the field then draws conclusions that are general in nature. This research is descriptive-analytical, namely the risk-seeking to harmonize the harmony of soldiers' husband and wife in Korem 132 / Tadulako. research. The results showed that the harmony of the wife's husband and wife in Korem 132 / Tadulako Perspective of the Islamic Law was in accordance with the Islamic law mentioned in QS Ar-Ruum (30): 21 which explained about pleasant-sounding family. From a legal perspective, TNI regulation contributes to improving the husband's relationship with the wife of the soldier because the rules that apply to soldiers and persist must be correlated with each other so that a happy family in the environment is realized.